The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.inorgchem.7b03215
|View full text |Cite
|
Sign up to set email alerts
|

Higher Flexibility of Glu-172 Explains the Unusual Stereospecificity of Glyoxalase I

Abstract: Despite many studies during the latest two decades, the reason for the unusual stereospecificity of glyoxalase I (GlxI) is still unknown. This metalloenzyme converts both enantiomers of its natural substrate to only one enantiomer of its product. In addition, GlxI catalyzes reactions involving some substrate and product analogues with a stereospecificity similar to that of its natural substrate reaction. For example, the enzyme exchanges the pro- S, but not the pro- R, hydroxymethyl proton of glutathiohydroxya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…This confirms the higher basicity of Glu-172 compared to Glu-99, as was previously proposed. [23][24][25][26] The big-QM energies of the four states are compared in Table 1, showing that the S1, S2 and R2 states are almost degenerate, whereas the R1 state is ~4 kcal/mol less stable than the others. In the latter, both protons (H1 and H2) point toward Glu-99, which may destabilize it by steric effects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This confirms the higher basicity of Glu-172 compared to Glu-99, as was previously proposed. [23][24][25][26] The big-QM energies of the four states are compared in Table 1, showing that the S1, S2 and R2 states are almost degenerate, whereas the R1 state is ~4 kcal/mol less stable than the others. In the latter, both protons (H1 and H2) point toward Glu-99, which may destabilize it by steric effects.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the three studies indicated that the higher basicity and flexibility of Glu-172 may explain the special stereospecificity of GlxI. Despite all previous studies, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] there is not any computationally or experimentally confirmed mechanism for the reaction of the R enantiomer of the normal substrate of GlxI. Moreover, there are two opposing mechanisms for the S substrate and they are based on either a rather primitive ab initio method (HF/4-31G) or a small model of the active site with no constraints on the residues during optimization processes.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations